2020
DOI: 10.3233/jad-191138
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Lifetime History of Traumatic Brain Injury Among Older American and Irish Adults at Risk for Dementia: Development and Validation of a Web-Based Survey

Abstract: Background: Traumatic brain injury (TBI) is an established risk factor for dementia but mechanisms are uncertain. Accurate TBI exposure classification is critical for cognitive aging research studies seeking to discover mechanisms and treatments of post-TBI dementia. Brief TBI screens, commonly used in epidemiological studies of cognitive aging, are insensitive, leading to exposure mis-classification. Comprehensive TBI interviews, while more sensitive, may be impractical. Objective: We aimed to develop and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…We evaluated clinically normal older adults without significant health comorbidities and with well-characterized head trauma history, Aβ-PET scans, and cognitive testing. Unique facets of our study included (1) a standardized and validated collection of lifelong head trauma exposure using the OA OSU TBI-ID (Gardner et al 2020), (2) a wider range of reported remote mTBI than similar studies (0, 1, or 2+), (3) investigating head trauma without classical mTBI symptoms like LOC or PTA (more akin to common diagnoses like "concussion"), (4) comprehensive and validated neuropsychological test measures to evaluate cognition, (5) thorough characterization of participants as clinically normal, and (6) having a subgroup with longitudinal Aβ-PET data. We found no associations between remote mTBI and cortical Aβ burden.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We evaluated clinically normal older adults without significant health comorbidities and with well-characterized head trauma history, Aβ-PET scans, and cognitive testing. Unique facets of our study included (1) a standardized and validated collection of lifelong head trauma exposure using the OA OSU TBI-ID (Gardner et al 2020), (2) a wider range of reported remote mTBI than similar studies (0, 1, or 2+), (3) investigating head trauma without classical mTBI symptoms like LOC or PTA (more akin to common diagnoses like "concussion"), (4) comprehensive and validated neuropsychological test measures to evaluate cognition, (5) thorough characterization of participants as clinically normal, and (6) having a subgroup with longitudinal Aβ-PET data. We found no associations between remote mTBI and cortical Aβ burden.…”
Section: Discussionmentioning
confidence: 99%
“…Aging studies like ours directly measure long-term outcomes through comprehensive collection of cognitive and neurodegenerative (e.g., Aβ-PET) biomarker data, but often are less representative of the general population than epidemiologic studies due to recruitment and survival biases. Accurate characterization of head trauma history remains tenuous in many study protocols (Gardner et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations